Pengaruh Profitabilitas, Ukuran Perusahaan, dan Non Performing Loan terhadap Nilai Perusahaan Perbankan Konvensional - Reza, Elva Dwi; Hanifah, Azimah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The aim of this study is to analyze the effect of Return on Equity (ROE), firm size (SIZE), and Non-Performing Loans (NPL) on firm value, measured using Tobin's Q, in conventional banking companies during the 2019–2023 period. The study employs panel data analyzed through multiple linear regression using EViews software. The findings indicate that ROE exerts a partial positive effect on firm value, with a significance level that is not considered to be statistically significant. Conversely, SIZE demonstrates a significant positive effect, while NPL exhibits a negative but insignificant effect. The simultaneous influence of ROE, SIZE, and NPL on firm value is found to be significant. The practical implications of this research offer insights to investors in evaluating company performance through relevant financial indicators and assist company management in enhancing financial performance and firm value. It is important to note that the study's limitations stem from its focus on a specific period and sample size. This restricts the generalizability of the findings and underscores the necessity for future research that incorporates more extensive data sets and additional variables to achieve more comprehensive results.